Huerta escolar : una alternativa de integración stem para promover la comprensión lectora y resolución de problemas matemáticos (2017)
The current research was based on the implementation of a school orchard as an alternative to put together was is known as "STEM" (Science, Technology, Engineering and Mathematics) to promote within students from elementary school the comprehension of what they read and the ability to resolve mathematical conjectures through the preparation, design, cultivation, production and sale of vegetables. To accomplish our goal, the students were first asked to read the histores while they were visiting an orchard; meanwhile, they were asked to apply the content they were able to understand, among others, such as "area, units of measurements and thermal floors." In addition to it, they were tasted on solving mathematical conjectures which were included in the narratives they were given. They also answered questions of a literal, inferential, and critical nature. The research was carried out under the qualitative design of a historical-hermeneutical approach within a case study. We involved five students from a Rural Elementary School located in the Municipality of Fosca, Cundinamarca and from a District Institution located in the town of Usme, Bogota-Colombia...